1992
DOI: 10.1017/s0952523800010786
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin synthesis and accumulation by neurons of the anuran retina

Abstract: Serotonin-synthesizing and serotonin-accumulating neurons were studied in the retinas of Xenopus laevis and Bufo marinus. All previously identified cell types exhibiting serotonin-like immunoreactivity (SLI) were labeled by intravitreal injection of 5,7-dihydroxytryptamine (5,7-DHT). They included two amacrine cell types (large and small) in both species, and one bipolar cell type in Xenopus. Incubation of retinas in culture medium in the ambient light reduced SLI in amacrine cells and enhanced the labeling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…In the present study we showed that only a portion of 5HT-immunoreactive cells contained GABA. We assume that both 5HT-synthesizing and -accumulating neurons (ZHU et al, 1992) colocalize with GABA in the Bufo retina. It has been demonstrated recently that the large-sized 5HT-synthesizing amacrine cell type is immunoreactive for microtubule-associated protein 2 (MAP2) in Bufo retina (GABRIEL et al, 1992b); however, no overlap between MAP2-and GABAimmunoreactive cells has been found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study we showed that only a portion of 5HT-immunoreactive cells contained GABA. We assume that both 5HT-synthesizing and -accumulating neurons (ZHU et al, 1992) colocalize with GABA in the Bufo retina. It has been demonstrated recently that the large-sized 5HT-synthesizing amacrine cell type is immunoreactive for microtubule-associated protein 2 (MAP2) in Bufo retina (GABRIEL et al, 1992b); however, no overlap between MAP2-and GABAimmunoreactive cells has been found.…”
Section: Discussionmentioning
confidence: 99%
“…The latter antibody, apart from phenylalanine hydroxylase which is not present in nervous tissue, recognizes tryptophan 5-hydroxylase and tyrosine hydroxylase (HAAN et al, 1987). Thus with some precaution, this antibody can be used as a marker for 5HT-synthesizing cells in the anuran retina (ZHu et al, 1992). The primary antibodies were applied overnight at room temperature, the sections then being washed in PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin (5-hydroxytryptamine; 5-HT) is one of the monoamine neurotransmitters in the retina, which is better represented in lower than higher vertebrate retinas (Osborne et al 1982). It is released by serotoninergic amacrine cells obtained in the retinas of many species (Ehinger 1983, Zhu et al 1992, Hurd and Eldred 1993, Gábriel 2000, Vigh et al 2000. Some serotonin-accumulating neurons are found among horizontal and bipolar cells, but it is thought that they are only able to transport and metabolize, but not synthesize serotonin (Marc et al 1988, Zhu et al 1992, Wilhelm et al 1993, Schutte 1994, Ghai et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is released by serotoninergic amacrine cells obtained in the retinas of many species (Ehinger 1983, Zhu et al 1992, Hurd and Eldred 1993, Gábriel 2000, Vigh et al 2000. Some serotonin-accumulating neurons are found among horizontal and bipolar cells, but it is thought that they are only able to transport and metabolize, but not synthesize serotonin (Marc et al 1988, Zhu et al 1992, Wilhelm et al 1993, Schutte 1994, Ghai et al 2009). Serotonin is also released by retinopetal axons that originate in dorsal raphe in fishes, rodents and primates (Villar et al 1987, Shen and Semba 1994, Lima and Urbina 1998, Gastinger et al 2005.…”
Section: Introductionmentioning
confidence: 99%